Real-time monitoring of DNA G-quadruplexes in living cells with a small-molecule fluorescent probe. Issue 15 (31st July 2018) - Zhang, Suge; Sun, Hongxia; Wang, Lixia; Liu, Yan; Chen, Hongbo; Li, Qian; Guan, Aijiao; Liu, Meirong; Tang, Yalin
Abstract: G-quadruplex DNA has been viewed as a prospective anti-cancer target owing to its potential biological relevance. Real-time monitoring of DNA G-quadruplex structures in living cells can provide valuable insights into the relationship between G-quadruplex formation and its cellular consequences. However, the probes capable of detecting DNA G-quadruplexes in living cells are still very limited. Herein, we reported a new fluorescent probe, IMT, for real-time visualization of DNA G-quadruplex structures in living cells. Using IMT as a fluorescent indicator, the quantity changes of DNA G-quadruplex at different points in time during continuous cellular progression responding to Aphidicolin and Hydroxyurea treatment have been directly visualized. Our data demonstrate that IMT will be a valuable tool for exploring DNA G-quadruplexes in live cells. Further application of IMT in fluorescence imaging may reveal more information on the roles of DNA G-quadruplexes in biological systems.